A review of the clinical experience with CMN-001, a tumor RNA loaded dendritic cell immunotherapy for the treatment of metastatic renal cell carcinoma - Mark DeBenedette; Alicia Gamble; Marcus Norris; Joe Horvatinovich; Charles A. Nicolette (Taylor & Francis Group, 2023)
Engineering dendritic cells (DCs) to treat cancer is a long sought-after goal for cell-based immunotherapies. In this review, we focus on the experience with CMN-001, formally AGS-003, a DC-based immunotherapy, employing autologous DC electroporated with autologous tumor RNA to treat subjects with metastatic renal cell carcinoma (mRCC). We will review the early clinical development of CMN-001 up to and including deployment in a multicenter phase 3 study and provide a rationale to continue the development of CMN-001 in an ongoing randomized phase 2 study. The synergy between CMN-001 and everolimus observed in the phase 3 study provides an opportunity to design a phase 2b study building on the mechanism of action of CMN-001 and underlying immune and clinical outcomes revealed in the earlier studies. The design of the phase 2b study combines CMN-001 with first-line checkpoint inhibition therapy and second line lenvatinib/everolimus in poor-risk mRCC subjects.